Uji Cepat untuk Padi Toleran Suhu Rendah Menggunakan Thermogradientbar - ROHAENI, WAGE R.; NAFISAH, NAFISAH; HAIRMANSIS, A.; LESTARI, PENI (Agrotrop : Journal on Agriculture Science; Vol 6 No 1 (2016), 2016)
Quick Evaluation for Cold Tolerant Line By Using Thermogradientbar. Lowtemperature stress was the main obstacle for rice growth in high elevation. Low temperaturestress greatly affect the vegetatif growth stage and generatif. There were required screening /quick test to determine the tolerance genotype for low temperature stress. Thermogradientbaris one quick screening tool that could potentially be used in the rice in the vegetatif phase.This study aimed to evaluate quickly for getting the tolerant rice lines on low temperaturestress. The study was conducted in November-December 2015 Biology Laboratory, LIPI. Atotal of 15 lines of upland rice and 3 checks were used in the testing. Gradient temperature onthermogradientbar tool were 12, 17, 18, 21, 22, 25, 26, 28, 31 oC. Seeds of each strain testedwith 5 replications. The number of replicates results show low temperature stress began tolook at the temperature of 18 oC. Genotype G3 (B12165D-MR-8-1-1-2), G4 (B11910D-MR-22-2), G5 (B14217F-MR-1), and G6 ( B14168E-MR-5) were a sensitive genotypes at atemperature <18 oC and a real contrast to the check-resistant white Sigambiri. StrainB12165D-MR-8-1-1-2 is the most sensitive by 23:14% germination.
Keywords: Quick evaluation; low temperature; vegetatif; rice